The role of training simulators in interventional radiation therapy (brachytherapy) training: A narrative review - Ferioli, Martina; Medici, Federica; Galietta, Erika; Forlani, Ludovica; Tagliaferri, Luca; Cilla, Savino; Cammelli, Silvia; Morganti, Alessio G.; Buwenge, Milly (Journal of Contemporary Brachytherapy, 2023)
Simulators have revolutionized medical education and training across various disciplines, offering unique advantages in skill acquisition and performance improvement. In the context of interventional radiation therapy (IRT), simulators have emerged as valuable tools for training healthcare professionals in these complex procedures. This narrative review summarized the available evidence on the use of simulators in IRT training, highlighting their impact on proficiency, engagement, and self-confidence as well as their benefits for medical physicists and radiation therapists. A systematic search was conducted in PubMed, resulting in inclusion of 10 papers published since 2009, with 5 of them published since 2020. Publications originated from centers in USA, Ireland, Switzerland, Canada, and Japan, covering a range of IRT settings, including general, prostate, and cervical IRT. The review demonstrated that simulators provide a controlled and realistic environment for skill acquisition, allowing healthcare professionals to practice procedures, optimize image quality, and enhance technical proficiency. The use of simulators addressed the barriers associated with limited caseload and procedural complexity, ultimately contributing to improved education and IRT training. While cost considerations may exist, simulators offer long-term cost-effective solutions, balancing the potential benefits in improving educational outcomes and patient care. Overall, simulators play a crucial role in IRT training, enhancing the skills and competence of healthcare providers and improving access to quality IRT care worldwide. Future research should focus on evaluating the long-term impact of simulation-based training on clinical outcomes and patient satisfaction, exploring different simulation models and training approaches, and addressing region-specific barriers to optimize the utilization of IRT.